S-(FeNiM) LDH / IF electrocatalyst, preparation method and application thereof
By developing S-(FeNiM)LDH/IF electrocatalyst, the existing OER catalysts have been solved, and the efficient and stable hydrogen production reaction of electrolytic water is achieved, and the industrial application of electrolytic water hydrogen production technology has been promoted.
Patent Information
- Application Number
- CN202411753033.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-02
Smart Images

Figure CN119571375A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrocatalytic water decomposition to produce hydrogen, and in particular to a S-(FeNiM)LDH / IF electrocatalyst, a preparation method and application thereof. Background Art
[0002] The development of clean renewable energy is an inevitable choice for human society to achieve sustainable development. Electrolysis of water to produce H2 is one of the effective methods for the production, storage and use of renewable energy in the future. The process includes the oxygen evolution reaction (OER, OH - -4e - →O2+2H2O, in alkaline medium) and the hydrogen evolution reaction (HER, 2H2O+2e - →2OH - +H2). Since the oxygen evolution reaction is a four-proton-electron transfer, the chemical reaction energy barrier is high and the reaction kinetics are slow, which is a bottleneck that hinders the realization of industrial electrolysis of water to produce H2. In addition, OER is also a basic reaction for electrochemical energy conversion and storage systems such as CO2 / N2 reduction, fuel cells, and metal-air batteries. Currently, the most effective OER catalysts are oxides of precious metals iridium and ruthenium (IrO2 and RuO2, etc.), but their scarcity and high cost severely limit their large-scale application. Therefore, the development of efficient and stable non-precious metal-based OER catalysts has important scientific value and broad application prospects.
[0003] The commonly used non-precious metal catalysts for OER are mainly Fe, Co and Ni based catalysts. Although people have been committed to studying the preparation methods and principles of such catalysts for many years, it is still challenging to develop non-precious metal based OER catalysts with high activity, high stability and low cost.
[0004] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that the current non-precious metal OER reaction catalyst has a high potential and a slow OER kinetic reaction, which hinders the realization of industrial electrolysis of water to produce H2. A S-(FeNiM)LDH / IF electrocatalyst, a preparation method and its application are provided.
[0006] In order to achieve the above object, the present invention discloses a S-(FeNiM)LDH / IF electrocatalyst, wherein M is Co or In, and the electrocatalyst is a three-dimensional layered nanosheet structure sheet.
[0007] The present invention also discloses a method for preparing the S-(FeNiM)LDH / IF electrocatalyst, comprising the following steps:
[0008] S1, put cobalt acetate or indium chloride, nickel acetate and foamed iron into a round-bottom flask, add H2O and ethanol, stir in an oil bath at 25°C for 30 min, and then slowly add Na2S solution;
[0009] S2, stirring the solution obtained in step S1 for 30 min, and then slowly adding a mixed solution consisting of NaOH and H2O;
[0010] S3, continue stirring the solution obtained in step S2 for 30 minutes, stir it to 80°C and then keep it warm and stir it for 0.5 to 3.5 hours, collect the product, wash it with H2O, and obtain a sample after drying. If cobalt acetate is used in step S1, S-(FeNiCo)LDH / IF electrocatalyst will be obtained, and if indium chloride is used, S-(FeNiIn)LDH / IF electrocatalyst will be obtained.
[0011] In the step S1, the amount of cobalt acetate or indium chloride is 0.5-1.26 mmol, the amount of nickel acetate is 0.5-1.26 mmol, the foam iron is a piece of 1×0.5 cm foam iron, the amount of H2O is 10-45 mL, the amount of ethanol is 5-40 mL, the amount of Na2S in the Na2S solution is 2.5-12.5 mg, and the amount of H2O is 2.5 mL.
[0012] In the step S1, the amount of cobalt acetate or indium chloride is 0.36 mmol, the amount of nickel acetate is 0.90 mmol, the foam iron is a piece of 1×0.5 cm foam iron, the amount of H2O is 35 mL, the amount of ethanol is 15 mL, the amount of Na2S in the Na2S solution is 7.5 mg, and the amount of H2O is 2.5 mL.
[0013] In the step S2, the amounts of NaOH and H2O in the mixed solution of NaOH and H2O are 30-100 mg and 2.5 mL, respectively.
[0014] In the step S2, the amounts of NaOH and H2O in the mixed solution of NaOH and H2O are 50 mg and 2.5 mL respectively.
[0015] In step S3, the insulation temperature is 80° C. and the insulation time is 2.5 h.
[0016] The present invention also discloses the application of the S-(FeNiM)LDH / IF electrocatalyst in OER, HER and overall water splitting reactions.
[0017] Compared with the prior art, the beneficial effects of the present invention are:
[0018] 1. The preparation process of the catalyst is simple: The preparation process of S-(FeNiM)LDH / IF (M=Co, In) is simple and is completed by the "seed" assisted method. Cobalt acetate (or indium chloride), nickel acetate, and foamed iron are used as raw materials. First, cobalt acetate and nickel acetate are dissolved in H2O and ethanol at a temperature of 25°C. After reacting for 30 minutes, Na2S solution is slowly added and the reaction is continued for 30 minutes. NaOH solution is slowly added dropwise and reacted for 30 minutes. The temperature is raised to 80°C and reacted for 2.5 hours to obtain a composite material S-(FeNiM)LDH / IF (M=Co, In) with a layered nanosheet structure.
[0019] 2. The present invention establishes a redox equilibrium system, which has a simple composition and includes H2O, ethanol, Na2S and O2 in the air, and can effectively regulate the microscopic morphology and electronic structure of S-(FeNiM)LDH / IF(M=Co,In). The product S-(FeNiM)LDH / IF(M=Co,In) after regulation has a nanosheet structure. The Na2S in this equilibrium system is reducing, and the O2 in the air is oxidizing, which can effectively regulate the electronic structure of S-(FeNiM)LDH / IF(M=Co,In). In the product S-(FeNiM)LDH / IF(M=Co,In) after regulation, sulfur exists in an oxidized form, and the valence states of iron, nickel and cobalt are mainly +2 and +3. The microstructure and unique electronic structure of the S-(FeNiM)LDH / IF(M=Co,In) nanosheet are the main reasons why it can greatly improve the OER electrochemical performance;
[0020] 3. High OER catalytic activity: When the S-(FeNiCo)LDH / IF prepared by the present invention is used for OER reaction, the test equipment is an electrochemical workstation, the working electrode is the S-(FeNiCo)LDH / IF electrode prepared above, the counter electrode is a platinum sheet electrode (1×2cm), the reference electrode is a Hg / HgO electrode, and the electrolyte is a 1M KOH solution. Under the above test conditions, the current density reaches 1000mA·cm -2 The corresponding OER reaction overpotential is only 288 mV, while under the same test conditions, (FeNiCo)LDH / IF is -2 The corresponding overpotential at the current density is 357mV. In comparison, the OER electrochemical performance of S-(FeNiCo)LDH / IF is greatly improved. Not only that, compared with other catalysts, S-(FeNiCo)LDH / IF can also be listed as one of the OER catalysts with better electrochemical performance; and S-(FeNiCo)LDH / IF has good catalytic stability: after 5000 cycles of cyclic voltammetry and 130h it test, the OER performance has not been significantly reduced;
[0021] 4. High HER catalytic activity: The present invention also uses a similar preparation method to prepare a sulfur-doped iron-nickel-indium layered hydroxide (S-(FeNiIn)LDH / IF) composite material. When the S-(FeNiIn)LDH / IF prepared by the present invention is used for HER reaction, the test equipment is an electrochemical workstation, the working electrode is the S-(FeNiIn)LDH / IF electrode prepared above, the counter electrode is a platinum sheet electrode (1×2cm), the reference electrode is a Hg / HgO electrode, and the electrolyte is a 1M KOH solution. Under the above test conditions, the current density reaches 100mA·cm -2 The corresponding HER reaction overpotential is only 174 mV, while under the same test conditions, (FeNiCo)LDH / IF at 100 mA cm -2 The corresponding overpotential at the current density is 232mV. In comparison, the electrochemical performance of S-(FeNiIn)LDH / IF is greatly improved. In addition, compared with other catalysts, S-(FeNiIn)LDH / IF is also one of the HER electrocatalysts with better electrochemical performance; and S-(FeNiIn)LDH / IF has good catalytic stability: after 5000 cycles of cyclic voltammetry, the HER performance has not been significantly reduced;
[0022] 5. Good water electrolysis performance: The S-(FeNiCo)LDH / IF composite material prepared by the present invention is used as the anode, and the S-(FeNiIn)LDH / IF composite material prepared by the present invention is used as the cathode to form an electrolytic cell (S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF), which is used for water electrolysis and has a good catalytic effect. The test equipment is an electrochemical workstation, and the electrolyte is 1M KOH solution. When the current density reaches 500mA·cm -2 When S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF has a water electrolysis reaction potential of only 1.74 V, while under the same test conditions, (FeNiCo)LDH / IF||(FeNiCo)LDH / IF has a water electrolysis reaction potential of only 1.74 V at 500 mA·cm -2 The corresponding potential at the current density is 1.99V. In comparison, the electrolytic water performance of S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF is greatly improved. Not only that, compared with other catalysts, S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF can also be listed as one of the catalysts with the best electrolytic water performance. Moreover, the catalytic stability of S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF electrolytic water is good. After 145h it test, the performance of electrolytic water has not been significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 SEM images of S-(FeNiCr)(OH)2 / IF with different Cr dosages (a 2.5%, b 5.0%, c 7.5%, d 10.0%, e 12.5%, f 28.5%)
[0024] Figure 2 SEM images of catalysts with different elements: (a) S-(FeNiAl)(OH)2 / IF, (b) S-(FeNiCu)
[0025] SEM images of (OH)2 / IF, (c) S-(FeNiSr)(OH)2 / IF, and (d) S-(FeNiMn)(OH)2 / IF;
[0026] Figure 3 are SEM photos of catalysts of different elements, (a) is the SEM image of Example 34, (b) is the SEM image of Example 33, (c) is the SEM image of Example 36, (d) is the SEM image of Example 32, (e) is the SEM image of Example 31, and (f) is the SEM image of Example 38;
[0027] Figure 4 OER overpotentials of catalysts synthesized from different elements (a) S-(FeNiIn)LDH / IF, (b) S-(FeNiZn)LDH / IF, (c) S-(FeNiV)LDH / IF, (d) S-(FeCoIn)LDH / IF, (e) S-(FeCoZn)LDH / IF, (f) S-(FeCoV)LDH / IF, (g) (FeNiIn)LDH / IF, (h) (FeCoIn)LDH / IF, (i) S-(FeNi)LDH / IF, (j) S-(FeCo)LDH / IF, (k) (FeNi)LDH / IF, (l) (FeCo)LDH / IF, (m) (FeNiCo)S / IF, (n) (FeNiCo)LDH / IF, (o) S-(FeNiCo)LDH / IF;
[0028] Figure 5 Comparison of Tafel slopes of catalysts of different elements synthesized experimentally
[0029] Figure 6 The preparation mechanism diagram of S-(FeNiCo)LDH / IF;
[0030] Figure 7 This is a SEM photograph of S-(FeNiCo)S-seed / IF prepared in Example 30;
[0031] Figure 8 XPS graph of S-(FeNiCo)S-seed / IF prepared in Example 30: (a) Fe 2p peak curve, (b) Ni 2p peak curve, (c) Co 2p peak curve, (d) S 2p peak curve;
[0032] Fig. 9 Electron microscope photos of the samples: (a) SEM photo of foamed iron, (b, c) SEM photos of S-(FeNiCo)LDH / IF prepared in Example 3 (b, c have different magnifications), (d) TEM photo of S-(FeNiCo)LDH / IF prepared in Example 3, (e) HRTEM photo of S-(FeNiCo)LDH / IF prepared in Example 3, (f) SAED diffraction rings of S-(FeNiCo)LDH / IF prepared in Example 3;
[0033] Fig.10 Raman spectrum and XPS curve of S-(FeNiCo)LDH / IF prepared in Example 3: (a) Raman spectrum; (b) XPS S2p peak curve, (c) XPS Ni2p peak curve, (d) XPS Co2p peak curve, (e) XPS Fe2p peak curve, and (f) XPS O1s peak curve.
[0034] Fig.11 Electron microscopic images of the (FeNiCo)LDH / IF prepared in Example 28: (a, b) SEM images, (c) TEM images, (d) HRTEM images;
[0035] Fig.12 SEM photos of S-(FeNiCo)LDH / IF prepared with different Na2S dosages: (a) 2.5 mg Na2S (Example 1), (b) 5.0 mg Na2S (Example 2), (c) 10 mg Na2S (Example 4), (d) 12.5 mg Na2S (Example 5), the scale bars in the figures are 2 μm;
[0036] Fig.13 (a) SEM photo and (b) TEM photo of S-(FeNiIn)LDH / IF prepared in Example 15;
[0037] Fig.14The OER performance of the prepared samples: (a) LSV curves of the OER reaction of S-(FeNiCo)LDH / IF (prepared in Example 3), S-(FeNiIn)LDH / IF (prepared in Example 15), (FeNiCo)LDH / IF (prepared in Example 28), and (FeNiIn)LDH / IF (prepared in Example 31) (electrolyte: 1 M KOH), (b) LSV curves of these samples at a current density of 1000 mA cm -2 (c) the corresponding overpotential of these samples, (c) the Tafel slope of the OER reaction, (d) the comparison of the activity area (ECSA) of S-(FeNiCo)LDH / IF (prepared in Example 3) and (FeNiCo)LDH / IF (prepared in Example 28), (e) the LSV curve of S-(FeNiCo)LDH / IF (prepared in Example 3) before and after 5000 CV scans; (f) is the it curve of S-(FeNiCo)LDH / IF (prepared in Example 3).
[0038] Fig.15 HER performance of the prepared samples: (a) LSV curves of HER reaction of S-(FeNiIn)LDH / IF (prepared in Example 15), S-(FeNiCo)LDH / IF (prepared in Example 3), (FeNiIn)LDH / IF (prepared in Example 31) and (FeNiCo)LDH / IF (prepared in Example 28) (electrolyte: 1 M KOH); (b) HER reaction of the four samples prepared in Example 15, Example 3, Example 31 and Example 28 at a current density of 100 mA cm -2 (c) Tafel slope diagram of HER reaction of four samples prepared in Example 15, Example 3, Example 31 and Example 28, (d) comparison of LSV curves of S-(FeNiIn)LDH / IF before and after 5000 CV scans.
[0039] Fig.16 The electrolytic water performance of the samples: (a) LSV curves of S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF, S-(FeNiCo)LDH / IF||S-(FeNiCo)LDH / IF and (FeNiCo)LDH / IF||(FeNiCo)LDH / IF (electrolyte: 1 M KOH); (b) LSV curves of S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF, S-(FeNiCo)LDH / IF||S-(FeNiCo)LDH / IF and (FeNiCo)LDH / IF||(FeNiCo)LDH / IF at a current density of 500 mA cm -2(c) is the comparison between the actual and theoretical values of H2 and O2 produced by S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF; (d) is the it curve of S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF. DETAILED DESCRIPTION
[0040] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.
[0041] Example 1
[0042] The specific preparation steps of S-(FeNiCo)LDH / IF-1 are as follows:
[0043] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, and then slowly add 2.5mL of 1mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0044] Example 2
[0045] The specific preparation steps of S-(FeNiCo)LDH / IF-2 are as follows:
[0046] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 2mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0047] Example 3
[0048] The specific preparation steps of S-(FeNiCo)LDH / IF-3 are as follows:
[0049] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0050] Example 4
[0051] The specific preparation steps of S-(FeNiCo)LDH / IF-4 are as follows:
[0052] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 4mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0053] Example 5
[0054] The specific preparation steps of S-(FeNiCo)LDH / IF-5 are as follows:
[0055] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 5mg / mL Na2S solution (because sodium sulfide solution has S 2-, which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0056] Example 6
[0057] The specific preparation steps of S-(FeNiCo)LDH / IF-6 are as follows:
[0058] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 15mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, and then keep stirring for 2.5 hours. Collect the product, wash with deionized water, and dry to obtain the sample.
[0059] Example 7
[0060] The specific preparation steps of S-(FeNiCo)LDH / IF-7 are as follows:
[0061] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 40mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0062] Example 8
[0063] The specific preparation steps of S-(FeNiCo)LDH / IF-8 are as follows:
[0064] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 40mL of H2O and 5mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0065] Example 9
[0066] The specific preparation steps of S-(FeNiCo)LDH / IF-9 are as follows:
[0067] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 5mL of H2O and 40mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0068] Example 10
[0069] The specific preparation steps of S-(FeNiCo)LDH / IF-10 are as follows:
[0070] Weigh 0.5mmol of cobalt acetate and 1.26mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0071] Embodiment 11
[0072] The specific preparation steps of S-(FeNiCo)LDH / IF-11 are as follows:
[0073] Weigh 1.26mmol of cobalt acetate and 0.5mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0074] Example 12
[0075] The specific preparation steps of S-(FeNiCo)LDH / IF-12 are as follows:
[0076] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 0.5h, collect the product, wash with deionized water, and dry to obtain the sample.
[0077] Embodiment 13
[0078] The specific preparation steps of S-(FeNiCo)LDH / IF-13 are as follows:
[0079] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2-, which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, and then keep stirring for 3.5 hours. Collect the product, wash with deionized water, and dry to obtain the sample.
[0080] Embodiment 14
[0081] The specific preparation steps of S-(FeNiIn)LDH / IF-1 are as follows:
[0082] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 1.25mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0083] Embodiment 15
[0084] The specific preparation steps of S-(FeNiIn)LDH / IF-2 are as follows:
[0085] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0086] Example 16
[0087] The specific preparation steps of S-(FeNiIn)LDH / IF-3 are as follows:
[0088] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 20mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0089] Embodiment 17
[0090] The specific preparation steps of S-(FeNiIn)LDH / IF-4 are as follows:
[0091] Weigh 0.5mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0092] Embodiment 18
[0093] The specific preparation steps of S-(FeNiIn)LDH / IF-5 are as follows:
[0094] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 5mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2-, which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0095] Embodiment 19
[0096] The specific preparation steps of S-(FeNiIn)LDH / IF-6 are as follows:
[0097] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 45mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0098] Embodiment 20
[0099] The specific preparation steps of S-(FeNiIn)LDH / IF-7 are as follows:
[0100] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 5mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0101] Embodiment 21
[0102] The specific preparation steps of S-(FeNiIn)LDH / IF-8 are as follows:
[0103] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 40mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0104] Embodiment 22
[0105] The specific preparation steps of S-(FeNiIn)LDH / IF-9 are as follows:
[0106] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 1mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0107] Embodiment 23
[0108] The specific preparation steps of S-(FeNiIn)LDH / IF-10 are as follows:
[0109] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 5mg / mL Na2S solution (because sodium sulfide solution has S 2-, which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0110] Embodiment 24
[0111] The specific preparation steps of S-(FeNiIn)LDH / IF-11 are as follows:
[0112] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 15mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, and then keep stirring for 2.5 hours. Collect the product, wash with deionized water, and dry to obtain the sample.
[0113] Embodiment 25
[0114] The specific preparation steps of S-(FeNiIn)LDH / IF-12 are as follows:
[0115] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 40mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0116] Embodiment 26
[0117] The specific preparation steps of S-(FeNiIn)LDH / IF-13 are as follows:
[0118] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 0.5h, collect the product, wash with deionized water, and dry to obtain the sample.
[0119] Embodiment 27
[0120] The specific preparation steps of S-(FeNiIn)LDH / IF-14 are as follows:
[0121] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, and then keep stirring for 3.5 hours. Collect the product, wash with deionized water, and dry to obtain the sample.
[0122] Embodiment 28
[0123] The specific preparation steps of (FeNiCo)LDH / IF are as follows:
[0124] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put in a piece of foam iron (1×0.5cm), add 32.5mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 20mg / mL NaOH solution, continue stirring for 30min, then slowly heat to 80℃, keep stirring for 2.5h, collect the product, wash with deionized water, and dry to obtain the sample.
[0125] Embodiment 29
[0126] The specific preparation steps of (FeNiCo)S / IF are as follows:
[0127] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 32.5mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 121mg / mL Na2S solution (because sodium sulfide solution has S 2- , it is easily oxidized by O2 in the air and must be prepared and used immediately. Preparation too early in advance may cause errors). Continue stirring for 30 minutes, then slowly heat to 80°C, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0128] Embodiment 30
[0129] The specific preparation steps of (FeNiCo)S-seed / IF are as follows:
[0130] Weigh 0.36mmol of cobalt acetate and 0.90mmol of nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). After stirring for 30 minutes, the product was collected, washed with deionized water, and dried to obtain a sample.
[0131] Embodiment 31
[0132] The specific preparation steps of (FeNiIn)LDH / IF are as follows:
[0133] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 28.5mL H2O and 15mL ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, slowly drop 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30min, slowly raise the temperature to 80℃, then keep stirring for 2.5h, collect the product, wash with deionized water, and dry to obtain the sample.
[0134] Embodiment 32
[0135] The specific preparation steps of (FeCoIn)LDH / IF are as follows:
[0136] Weigh 1.26mmol of cobalt acetate into a round-bottom flask, then put in a piece of foamed iron (1×0.5cm), add 28.5mL of H2O and 15mL of ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, slowly drop 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30min, slowly raise the temperature to 80℃, then keep stirring for 2.5h, collect the product, wash with deionized water, and dry to obtain the sample.
[0137] Embodiment 33
[0138] The specific preparation steps of (FeCo)LDH / IF are as follows:
[0139] Weigh 1.26mmol of cobalt acetate into a round-bottom flask, then put in a piece of foamed iron (1×0.5cm), add 32.5mL of H2O and 15mL of ethanol, stir at 25°C for 30min, slowly drop 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30min, slowly raise the temperature to 80°C, then keep stirring for 2.5h, collect the product, wash with deionized water, and dry to obtain the sample.
[0140] Embodiment 34
[0141] The specific preparation steps of (FeNi)LDH / IF are as follows:
[0142] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 32.5mL H2O and 15mL ethanol, stir at 25℃ for 30min, slowly drop 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30min, slowly raise the temperature to 80℃, then keep stirring for 2.5h, collect the product, wash with deionized water, and dry to obtain the sample.
[0143] Embodiment 35
[0144] The specific preparation steps of S-(FeNi)LDH / IF are as follows:
[0145] Weigh 1.26mmol nickel acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL H2O and 15mL ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2-, which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0146] Embodiment 36
[0147] The specific preparation steps of S-(FeCo)LDH / IF are as follows:
[0148] Weigh 1.26mmol of cobalt acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0149] Embodiment 37
[0150] The specific preparation steps of S-(FeCoZn)LDH / IF are as follows:
[0151] Weigh 1.26mmol of cobalt acetate and 0.14mmol of zinc acetate, put them into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL of H2O and 15mL of ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0152] Embodiment 38
[0153] The specific preparation steps of S-(FeNiZn)LDH / IF are as follows:
[0154] Weigh 1.26mmol nickel acetate and 0.14mmol zinc acetate, put them into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL H2O and 15mL ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0155] Embodiment 39
[0156] The specific preparation steps of S-(FeNiV)LDH / IF are as follows:
[0157] Weigh 1.26mmol nickel acetate and put it into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 30mL H2O and 15mL ethanol, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately, and preparing too early in advance may cause errors), stir for 30 minutes, and slowly drop 2.5mL of A solution (composed of 20mg / mL NaOH solution and 0.14mmol of ammonium metavanadate). Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0158] Embodiment 40
[0159] The specific preparation steps of S-(FeCoV)LDH / IF are as follows:
[0160] Weigh 1.26 mmol of cobalt acetate and put it into a round-bottom flask, then put a piece of foam iron (1×0.5 cm), add 30 mL of H2O and 15 mL of ethanol, stir at 25°C for 30 min, and then slowly add 2.5 mL of 3 mg / mL Na2S solution (because sodium sulfide solution has S 2-, which is easily oxidized by O2 in the air, must be prepared and used immediately, and preparing too early in advance may cause errors), stir for 30 minutes, and slowly drop 2.5mL of A solution (composed of 20mg / mL NaOH solution and 0.14mmol of ammonium metavanadate). Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0161] Embodiment 41
[0162] The specific preparation steps of S-(FeCoIn)LDH / IF are as follows:
[0163] Weigh 1.26mmol of cobalt acetate into a round-bottom flask, then put a piece of foam iron (1×0.5cm), add 26mL of H2O and 15mL of ethanol, add 4mL of 5mg / mL indium chloride solution, stir at 25℃ for 30min, then slowly add 2.5mL of 3mg / mL Na2S solution (because sodium sulfide solution has S 2- , which is easily oxidized by O2 in the air, must be prepared and used immediately. Preparation too early in advance may cause errors). Stir for 30 minutes, and slowly add 2.5mL of 20mg / mL NaOH solution. Continue stirring for 30 minutes, slowly raise the temperature to 80℃, then keep stirring for 2.5 hours, collect the product, wash with deionized water, and dry to obtain the sample.
[0164] First, S-doped iron nickel chromium hydroxide (S-(FeNiCr)(OH)2 / IF) electrocatalyst, S-doped iron nickel aluminum hydroxide (S-(FeNiAl)(OH)2 / IF) electrocatalyst, S-doped iron nickel copper hydroxide (S-(FeNiCu)(OH)2 / IF) electrocatalyst, S-doped iron nickel copper hydroxide (S-(FeNiCu)(OH)2 / IF) electrocatalyst, S-doped iron nickel strontium hydroxide (S-(FeNiSr)(OH)2 / IF) electrocatalyst and S-doped iron nickel manganese hydroxide (S-(FeNiMn)(OH)2 / IF) electrocatalyst were prepared. However, no matter what the doping ratio is, a two-dimensional nanosheet structure cannot be obtained. As shown in the following figure ( Figure 1 and Figure 2 ) shows that its structure is irregular and in a state of large aggregates.
[0165] In addition, the experiment continues to explore new metal elements (such as vanadium, zinc, indium, cobalt, etc.) to participate in the doping of iron-nickel based catalysts. After a large number of experimental attempts, such as Figure 3As shown in the figure, a series of electrocatalytic materials with nanosheet structures were synthesized, such as S-(FeNiCo)LDH / IF, S-(FeNiIn)LDH / IF, S-(FeCoZn)LDH / IF, etc.
[0166] In order to more comprehensively investigate the effect of element doping on the overall OER performance of the catalyst, electrocatalysts with different element compositions were synthesized experimentally, and the OER performance of these electrocatalysts was tested in 1M KOH solution. The overpotential and Tafel slope were compared as shown in Figure 2. Figure 4 and Figure 5 As shown. Figure 4 It can be seen that at 1000mAcm -2 At the current density, S-(FeNiCo)LDH / IF has the smallest OER overpotential (288mV) among these electrocatalysts; Figure 5 It can be seen that S-(FeNiCo)LDH / IF has the smallest Tafel slope value, indicating that S-(FeNiCo)LDH / IF electrocatalyst has the optimal OER kinetic process.
[0167] Figure 6 The preparation process of S-(FeNiCo)LDH / IF composite material is shown in Figure 1. First, the foamed iron is immersed in a mixed solution of H2O and ethanol containing cobalt acetate and nickel acetate. The foamed iron gives out iron ions under acidic conditions. After adding Na2S solution, S 2- It reacts with iron ions, nickel ions and cobalt ions, and S also reacts with O2 in the air to form iron-cobalt-nickel sulfides on the surface of the foamed iron (iron-cobalt-nickel sulfides are recorded as (FeNiCo)S-seed, and the composite material composed of iron-cobalt-nickel sulfides and foamed iron is recorded as (FeNiCo)S-seed / IF). With (FeNiCo)S-seed as the nucleation "seed", after adding NaOH, it can continue to react and grow to form S-(FeNiCo)LDH / IF.
[0168] Figure 7 This is a scanning electron microscope (SEM) photograph of the (FeNiCo) S-seed / IF prepared in Example 30. It can be seen that its microscopic morphology is nanosheet-like. Figure 8 From the XPS curve of (FeNiCo)S-seed / IF prepared in Example 30, it can be seen that the iron, cobalt and nickel therein are mainly in the +2 and +3 valence states, and the sulfur mainly appears in the oxidized form.
[0169] Fig. 9This is an electron microscope photo of S-(FeNiCo)LDH / IF prepared in Example 3. It can be clearly seen that a large number of sulfur-doped iron-cobalt-nickel hydroxide nanosheets (S-(FeNiCo)LDH) grow on the surface of the foamed iron. These nanosheets are directly stacked together to form three-dimensional nanospheres.
[0170] Fig.10 is the XPS curve of S-(FeNiCo)LDH / IF prepared in Example 3. Fig.10 It can be seen that the nanosheets grown on the surface of the foamed iron are mainly composed of iron, cobalt, nickel, sulfur and oxygen elements; and iron, cobalt and nickel are mainly +2 plus and +3 valence, and sulfur is mainly in the oxidation state. The molar percentages of iron, cobalt, nickel and sulfur are 55.29%, 37.22%, 7.06% and 0.44% respectively (Table 1). After the introduction of S element, the average valence state of Ni element decreased from 2.72 to 2.30 (Table 2), the average valence state of Co element changed relatively little, from 2.61 to 2.51 (Table 3), and the average valence state of Fe element increased from 2.29 to 2.65 (Table 4). It can be seen that after the introduction of S element, the electronic structure of the prepared sample changed, and the electrons mainly flowed from Fe element to Ni element. The change of electronic structure will enhance the activity of active sites, thereby improving the OER performance.
[0171] In order to investigate the role of (FeNiCo)S-seed, layered hydroxides of iron, cobalt and nickel ((FeNiCo)LDH) were prepared through comparative experiments. That is, no Na2S was added during the preparation of S-(FeNiCo)LDH / IF, that is, no nucleation "seed" was introduced, and the microscopic morphology of the obtained product was significantly different. Fig.11 This is an electron microscope photo of the (FeNiCo)LDH / IF prepared in Example 28. Fig.11 (b) It can be clearly seen that without nucleation "seeds", the number of nanosheets grown is small and the area of the nanosheets is small. Therefore, (FeNiCo)S-seed promotes the growth of (FeNiCo)LDH. In addition, Fig.11 (d) The lattice spacing of 0.259 nm corresponds to the (012) plane of (FeNiCo)LDH. After the introduction of nucleation "seeds" during the preparation process, its lattice spacing becomes 0.266 nm ( Fig. 9 (e)), mainly because the radius of S atoms is larger than that of O atoms, and after the introduction of larger atoms, the lattice spacing increases slightly. This also shows that S atoms are uniformly doped into the lattice of (FeNiCo)LDH. Figure 7 S-(FeNiCo)LDH / IF prepared with different Na2S dosages. It can be seen that when the Na2S dosage is 7.5 and 10 mg, the thickness of the nanosheets is smaller.
[0172] Using the same method, sulfur-doped iron-nickel-indium layered hydroxide (S-(FeNiIn)LDH / IF) was also prepared. Fig.13 This is the electron microscope photograph of S-(FeNiIn)LDH / IF prepared in Example 15, which clearly shows a two-dimensional nanosheet structure.
[0173] Table 1 Mass percentage of each element in nanosheet S-(FeNiCo)LDH and (FeNiCo)LDH (measured by ICP-MS method)
[0174] Sample S (wt%) Fe(wt%) Co(wt%) Ni(wt%) S-(FeNiCo)LDH 0.44 55.29 7.06 37.22 (FeNiCo)LDH - 75.25 6.09 18.66
[0175] Table 2 Valence of Ni in S-(FeNiCo)LDH / IF and (FeNiCo)LDH / IF
[0176] Sample <![CDATA[Ni 2+ ]]> <![CDATA[Ni 3+ ]]> Average states (FeNiCo)LDH / IF 28.27% 71.73% 2.72 S-(FeNiCo)LDH / IF 69.97% 30.03% 2.30
[0177] Table 3 Valence of Co in S-(FeNiCo)LDH / IF and (FeNiCo)LDH / IF
[0178] Sample <![CDATA[Co 2+ ]]> <![CDATA[Co 3+ ]]> Average states (FeNiCo)LDH 39.01% 60.99% 2.61 S-(FeNiCo)LDH 49.15% 50.85% 2.51
[0179] Table 4 Valence of Fe element in S-(FeNiCo)LDH / IF and (FeNiCo)LDH / IF
[0180]
[0181] Electrochemical performance of S-(FeNiM)LDH / IF(M=Co,In):
[0182] First, the OER performance of S-(FeNiCo)LDH / IF prepared in Example 3 was tested. Under the condition of 1M KOH as electrolyte, the linear sweep voltammetry (LSV) curve measured by a three-electrode electrochemical workstation is as follows: Fig.14 As shown in (a), the working electrode is S-(FeNiCo)LDH / IF, the counter electrode is a platinum electrode (1×2 cm), and the reference electrode is a Hg / HgO electrode. Fig.14 As can be seen from (a), the S-(FeNiCo)LDH / IF prepared in Example 3 has the best OER performance. The current density it generates in the entire scanning range is greater than that generated by the other three samples; the current density of S-(FeNiCo)LDH / IF, S-(FeNiIn)LDH / IF, (FeNiCo)LDH / IF and (FeNiIn)LDH / IF is 1000 mA cm -2 The corresponding overpotential is Fig.14As shown in (b), it can be seen that when the current density reaches 1000 mA cm -2 When S-(FeNiCo)LDH / IF has an overpotential of only 288 mV, under the same test conditions, S-(FeNiIn)LDH / IF, (FeNiIn)LDH / IF and (FeNiCo)LDH / IF have an overpotential of only 288 mV when the overpotential is 1000 mA·cm -2 The corresponding overpotentials at the current density were 313, 350 and 357 mV, respectively. In comparison, the OER performance of S-(FeNiCo)LDH / IF was greatly improved. Moreover, compared with other Fe-Co-Ni based electrocatalysts, under similar test conditions, S-(FeNiCo)LDH / IF can also be listed as one of the catalysts with better OER performance (Table 5). Fig.14 (c) is the Tafel slope diagram corresponding to the OER reaction of the samples prepared in Examples 3, 15, 28, and 31. It can be seen that the Tafel slope of the electrocatalyst S-(FeNiCo)LDH / IF among the prepared samples is the smallest, which is 23.9 mV dec. -1 The smaller the Tafel slope, the faster the current density increases, indicating faster catalyst kinetics and better catalytic activity. Fig.14 (d) is the electrocatalytic activity area (ECSA) bar graph of the samples prepared in Examples 3 and 28. It can be seen that the ECSA of S-(FeNiCo)LDH / IF is 2.90 times that of (FeNiCo)LDH / IF. The LSV curves of the S-(FeNiCo)LDH / IF prepared in Example 3 before and after 1000 scans by cyclic voltammetry (CV) are shown in FIG. Fig.14 (e) is used to test the stability of the catalyst. Fig.14 As can be seen in (e), there is almost no difference between the curves before and after scanning 1000 times, indicating good stability. Fig.14 (f)), its current density at 325 mV decreased by only 8%, further confirming its good stability.
[0183] Table 5 Comparison of OER performance of S-(FeNiCo)LDH / IF obtained in Example 3 and currently reported electrocatalysts under similar conditions
[0184]
[0185]
[0186] like Fig.15 (a) Fig.15 As shown in (b), the S-(FeNiIn)LDH / IF prepared in Example 15 has the best HER performance, which is 100 mA·cm-2 When S-(FeNiIn)LDH / IF has an overpotential of only 174 mV, under the same test conditions, S-(FeNiCo)LDH / IF, (FeNiIn)LDH / IF and (FeNiCo)LDH / IF have an overpotential of only 174 mV when the overpotential is 100 mA·cm -2 The corresponding overpotentials at the current density are 210, 217 and 317 mV, respectively. In comparison, the HER performance of S-(FeNiIn)LDH / IF is significantly improved. Fig.15 (c) is the Tafel slope bar graph of the four samples. It can be seen that the Tafel slope increases from 144.9 mV dec for (FeNiCo)LDH / IF to -1 It drops sharply to 48.9mV dec for S-(FeNiIn)LDH / IF -1 , indicating that the HER kinetics of the catalyst is much faster. The CV curve of S-(FeNiIn)LDH / IF prepared in Example 15 ( Fig.15 (d)) shows that the catalyst has good stability.
[0187] Finally, the S-(FeNiCo)LDH / IF prepared in Example 3 was used as the anode, and the S-(FeNiIn)LDH / IF prepared in Example 15 was used as the cathode to form a two-electrode water electrolysis device, and the water electrolysis performance of the electrocatalyst in this application was investigated. The electrolyte was 1M KOH. Fig.16 (a) is the LSV curve of S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF, S-(FeNiCo)LDH / IF||S-(FeNiCo)LDH / IF and (FeNiCo)LDH / IF||(FeNiCo)LDH / IF. Fig.16 (a) It can be seen that S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF has the best water electrolysis performance. -2 When S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF is used, the potential corresponding to S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF is only 1.74 V. However, under the same test conditions, (FeNiCo)LDH / IF||(FeNiCo)LDH / IF is 500 mA·cm -2 The corresponding potential at the current density is 1.99V. In comparison, the electrolytic water performance of S-(FeNiIn)LDH / IF has been greatly improved ( Fig.16(b)). In addition, as shown in Table 6, the S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF water electrolysis system requires an ultra-low voltage of 1.74 V to achieve a current density of up to 500 mA cm-1 compared with the recently reported water electrolysis catalysts. -2 . Fig.16 (c) is a comparison of the actual and theoretical values of H2 and O2 generated by S-(FeNiCo)LDH / IF||S-(FeNiIn)LDH / IF. It can be seen that the amount of H2 and O2 actually collected is close to 2:1, and the Faraday efficiency is almost close to 100%. Its electrolysis water it curve proves its good stability ( Fig.16 (d)).
[0188] Table 6 Different catalytic materials at 500 mA·cm -2 Comparison of overall water splitting activity under different current densities
[0189]
[0190] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.
Claims
1. A S-(FeNiM)LDH / IF electrocatalyst, characterized in that The M is Co or In, and the electrocatalyst is a three-dimensional layered nanosheet structure sheet.
2. A method for preparing the S-(FeNiM)LDH / IF electrocatalyst according to claim 1, characterized in that: The following steps are involved: S1, put cobalt acetate or indium chloride, nickel acetate and foamed iron into a round-bottom flask, add H2O and ethanol, stir in an oil bath at 25°C for 30 min, and then slowly add Na2S solution; S2, stirring the solution obtained in step S1 for 30 min, and then slowly adding a mixed solution consisting of NaOH and H2O; S3, continue stirring the solution obtained in step S2 for 30 minutes, stir it to 80°C and then keep it warm and stir it for 0.5 to 3.5 hours, collect the product, wash it with H2O, and obtain a sample after drying. If cobalt acetate is used in step S1, S-(FeNiCo)LDH / IF electrocatalyst will be obtained, and if indium chloride is used, S-(FeNiIn)LDH / IF electrocatalyst will be obtained.
3. A method for preparing the S-(FeNiM)LDH / IF electrocatalyst as claimed in claim 2, characterized in that: In the step S1, the amount of cobalt acetate or indium chloride is 0.5-1.26 mmol, the amount of nickel acetate is 0.5-1.26 mmol, the foam iron is a piece of 1×0.5 cm foam iron, the amount of H2O is 10-45 mL, the amount of ethanol is 5-40 mL, the amount of Na2S in the Na2S solution is 2.5-12.5 mg, and the amount of H2O is 2.5 mL.
4. The method for preparing a S-(FeNiM)LDH / IF electrocatalyst according to claim 2, characterized in that: In the step S1, the amount of cobalt acetate or indium chloride is 0.36 mmol, the amount of nickel acetate is 0.90 mmol, the foam iron is a piece of 1×0.5 cm foam iron, the amount of H2O is 35 mL, the amount of ethanol is 15 mL, the amount of Na2S in the Na2S solution is 7.5 mg, and the amount of H2O is 2.5 mL.
5. The method for preparing a S-(FeNiM)LDH / IF electrocatalyst according to claim 2, characterized in that: In the step S2, the amounts of NaOH and H2O in the mixed solution of NaOH and H2O are 30-100 mg and 2.5 mL, respectively.
6. The method for preparing a S-(FeNiM)LDH / IF electrocatalyst according to claim 2, characterized in that: In the step S2, the amounts of NaOH and H2O in the mixed solution of NaOH and H2O are 50 mg and 2.5 mL respectively.
7. The method for preparing a S-(FeNiM)LDH / IF electrocatalyst according to claim 2, characterized in that: In step S3, the insulation temperature is 80° C. and the insulation time is 2.5 h.
8. Use of the S-(FeNiM)LDH / IF electrocatalyst as claimed in claim 1 in OER, HER and overall water splitting reactions.
Citation Information
Patent Citations
Preparation of CoNiFeS-OH nano array material and application of CoNiFeS-OH nano array material in OER, UOR and full hydrolysis
CN113416973A
Method for preparing sulfur-doped porous NiFe-LDH electrocatalyst at room temperature
CN113789536A
Preparation method of Ni-CoFe LDHs alkaline electrolysis water oxygen evolution catalyst
CN118186489A
Method for preparing Fe-based water electrolysis oxygen evolution catalyst based on electrochemical corrosion engineering and application of Fe-based water electrolysis oxygen evolution catalyst
CN118814208A
Method for preparing supported catalyst and application thereof
WO2023279406A1
Cited By
Sulfur-doped nickel-cobalt-iron layered double hydroxide nanosheet array catalyst as well as preparation method and application thereof
CN120082913A